Psychic Repression Toward Death in Marwan Abboud’s Majnun Layla - As’ad, Zidan; Hidayatullah, Moch Syarif (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
Psychoanalytic studies on Arabic literary works have grown in recent years, yet the character of Layla has consistently been positioned as a passive object rather than an autonomous psychic subject. This study examines the psychic repression of Layla in the fourth act (al-Faṣl ar-Rābi’) of Marwan Abboud’s poetic drama Majnun Layla, aiming to trace how ego defense mechanisms operate not as fixed categories but as a dynamic process that accumulates across six scenes and produces death as its only resolution. A descriptive qualitative method is applied through close reading of Abboud’s original Arabic text, with Freud’s psychoanalytic framework covering id, ego, superego, and ego defense mechanisms as the analytical instruments. The analysis finds that Layla’s repression moves through identifiable phases: from rationalization and denial in the opening scenes, to sublimation giving way to collapsed hope following Qais’s letter, to external acceleration as Sa’d and Mahdi materialize the patriarchal superego and progressively eliminate every available exit for Layla, and finally to total ego collapse marked by delirium and a direct invocation of death. The findings show that Layla’s death is not a romantic inevitability but a consequence of accumulated psychic pressure sustained by the system surrounding her. This study concludes that repositioning Layla as the primary psychic subject opens a more precise reading of how patriarchal values operate through the repression of personal desire in Arabic literary tradition.